(untitled) (TEST Ticontre. Theory Text Translation, 2020)
The essay reconstructs the history of Elio Pagliarani’s twp journals, «Periodo ipotetico» and`«Ritmica», outlining the political-cultural scenario within which they were active. In particular, is highlighted the work done by Pagliarani himself, who accompanied and encouraged the transition from the neo-avant-garde generation to that of Gruppo 93.